2014
DOI: 10.21608/jpp.2014.53644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maturity Stage on Physical and Chemical Characteristics and Determination of Harvest Time of Sugar Snap Pea Pods

Abstract: The study aimed to investigate the effect ofmaturity stage on the nutritional quality and determination of the best maturity stage of sugar snap peassuitable for harvesting. Results showed that fresh weight of pods was increasedand then decreased.Length and width increased until 48, 32 days after flowering (DAF), respectively, and then decreased. Dry matter and crude fiber increased while chlorophyll and vitamin C decreased during pod development. Sugar content and SSC increased and then decreased while phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Previous studies have also revealed the nutritional potential of mangetout, not only for its protein content but also for its content of total soluble solids and antioxidant compounds such as polyphenols, ascorbic acid, fiber, phytoprostanes and phytofurans [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also revealed the nutritional potential of mangetout, not only for its protein content but also for its content of total soluble solids and antioxidant compounds such as polyphenols, ascorbic acid, fiber, phytoprostanes and phytofurans [12][13][14].…”
Section: Introductionmentioning
confidence: 99%